DESCRIPTION OF THE MALE OF Pseudomacrochiron Parvum (A. SCOTT, 1909) (COPEPODA, POECILOSTOMATOIDA) WITH REMARKS ON THE FEMALE - Mulyadi Mulyadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2008)
The male of Pseudomacrochiron parvum (A. Scott, 1909), which is unknown so far, is described and fi gured on specimens collected off Labuan, Sunda Strait (06º10’S 105º45’E), westward of the type locality in Indonesian waters, and expand the description of the female.